PENGEMBANGAN PERANGKAT PEMBELAJARAN KIMIA KELARUTAN DAN HASIL KALI KELARUTAN (Ksp) DENGAN PENDEKATAN SETS UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS DAN KREATIF SISWA - Setiyono, fiengky Priyo (JPP, 2011)
The basic consideration of this research is that the improvement of qualified humanresources needs a strong commitment in focusing and developing creativity whichactually everyone has it in the world. Chemistry assessment of solubility and solubilityproduct (Ksp) is difficult comprehended, because of comprehension student onmemorizing concept, and apply direct concept learned, so that expected its creativity alsowill expand. This research is kind of developing research, which develops learninginstruments visioned by SETS (Science, Environment, Technology, and Society). Themain purpose of this research is result chemistry learning instruments on solubility andsolubility product (Ksp) visioned by SETS, included: syllabus, lesson plan, module,evaluation instruments, CD of learning and to know the impact of creativity in learningresearch. The subject for this research is student of grade X.1 IPA. To understand theimprovement of creativity and learning outcome of students, the writer makesobservation and testing student understanding on the concept of solubility and solubilityproduct (Ksp). The responds from the subject on the learning process was obtained fromthe feedback of questionaire. Teachers have tought the students by implementing thelearning package. Result of students creativity observed was 46,3% at the beginning andincreased to 66,4% at the end. Creativity test result in tcalc 16,8. This value of 16,8 (morethan 2,04) means that there was a significant improvement of creativity after applying alearning instrument using learning process, the learning set/unit envisioned by SETS.From the whole result of the learning process, the learning set/unit envisioned by SETSshows improvement of learning result. Learning result test in tcalc 4,8. This value of 4,8(more than 2,04) mean that there was a significant improvement of learning outcome afterapplying the learning package using learning process, the learning set/unit envisionedby SETS.Keywords: creativity, learning process envisioned by SETS, learning result